Caveolin-1 Expression Ameliorates Nephrotic Damage in a Rabbit Model of Cholesterol-Induced Hypercholesterolemia. - Ya-Hui Chen (PLoS ONE, 2016)
Caveolin-1 (CAV-1) participates in regulating vesicular transport, signal transduction, tumor progression, and cholesterol homeostasis. In the present study, we tested the hypothesis that CAV-1 improves dyslipidemia, inhibits cyclophilin A (CypA)- mediated ROS production, prevents mitochondrial compensatory action and attenuates oxidative stress responses in cholesterol-induced hypercholesterolemia. To determine the role of CAV-1 in mediating oxidative and antioxidative as well as cholesterol homeostasis, hypercholesterolemic rabbits were intravenously administered antenapedia-CAV-1 (AP-CAV-1) peptide for 2 wk. AP-CAV-1 enhanced CAV-1 expression by ˃15%, inhibited CypA expression by ˃50% (P < 0.05) and significantly improved dyslipidemia, thus reducing neutral lipid peroxidation. Moreover, CAV-1 attenuated hypercholesterolemia-induced changes in mitochondrial morphology and biogenesis and preserved mitochondrial respiratory function. In addition, CAV-1 protected against hypercholesterol-induced oxidative stress responses by reducing the degree of oxidative damage and enhancing the expression of antioxidant enzymes. CAV-1 treatment significantly suppressed apoptotic cell death, as evidenced by the reduction in the number of terminal deoxynucleotidyl transferase dUTP nick end-labeling-positive cells. We concluded that CAV-1 plays a critical role in inhibiting CypA-mediated ROS production, improving dyslipidemia, maintaining mitochondrial function, and suppressing oxidative stress responses that are vital for cell survival in hypercholesterol-affected renal organs.